(untitled) (Research, Society and Development, 2021)
The work sought to understand the perception of the Pará population about the waste they produce and how they deal with it, aiming to understand the effects it causes in the socio-environmental environment; which, most of the times, is a problem for most Brazilian cities. For this purpose, anonymous data were analyzed through a virtual field research, where the descriptive quantitative method was used. The survey data were collected through the Google Forms platform, 435 people answered the questionnaire that contained 21 questions, divided into two categories: the personal identification of the respondent, and the population’s knowledge about the consumption and production of waste. Subsequently, all statistical data were analyzed using graphs and tables, and among the main results of the survey it was noted that among the majority of respondents there is a concern with environmental issues, but a part of those questioned are not aware of the what happens with the waste produced by them. Given this, there is a need to strengthen more policies on selective waste collection.